NANNOFOSSIL EVENTS AND STRATIGRAPHY OF THE ILAM FORMATION IN ZAGROS (SW IRAN) (Rivista italiana di Paleontologia e Stratigrafia, 2014)
Exploration studies of Cretaceous system in the Zagros region are very important due to the presence large hydrocarbon fields like the Ab-Teymur oilfield. The first data on the distribution of calcareous nannofossils in the Ilam Formation, belonging to the Bangestan Group in the Zagros Basin, are presented here. According to the distribution of calcareous nannofossils, the Upper Cretaceous deposits of the section are subdivided into three complete biostratigraphic units, namely: the Micula decussata (CC14-Late Coniacian), Reinhardtites anthophorus (CC15-late Early Santonian), Lucianorhabdus cayeuxii (CC16-Late Santonian) and base of CC17 zones. This record confirms the existence of biozone CC14 to basal CC17 of the zonation of Sissingh (1977), which suggests an age from Late Coniacian to Late Santonian for the studied sediments. Besides biostratigraphy, the presence of abundant calcareous nannofossils typical of warm climate and low latitude conditions in Ab-Teymur oilfield allows paleoenvironmental interpretations.